Financialisation at a watershed in the USA - Costas Lapavitsas; Ivan Mendieta-Mu\~noz (The University of Utah, Department of Economics, 2017)
Since the Great Recession of 2007-9 the financialisation of the US economy has reached a watershed characterised by stagnant financial profits, falling mortgage debt and rising public debt. The reliance of households on the formal financial system appears to have weakened for the first time in the post-war period. The financial sector has lacked the dynamism characteristic of the previous three decades and has become more reliant on the state, which has greatly increased its own indebtedness and has driven public interest rates close to zero. At the same time, state intervention has tightened the regulatory framework for big banks. The future path of financialisation in the USA will depend heavily on government policy with regard to state debt and to financial regulation.
Keywords: B50; E10; E44; G20; 330; financial profits; debt; financialisation; U.S. economy; household debt